2022
DOI: 10.1002/smi.3183
|View full text |Cite
|
Sign up to set email alerts
|

Stress, anxiety, emotion regulation and social support in parent‐child dyads prior to and during the onset of the COVID‐19 pandemic

Abstract: In March 2020, and in order to assess the impact of the COVID‐19 pandemic on stress and mental health in parent‐child dyads using pre‐pandemic measures, we recontacted participants from a 2019 study. A total of 136 dyads of Canadian parents (77% mothers, mean age = 44.48 y/o) and children (63% girls, 77% aged 10‐12 y/o and 23% aged 15‐17 y/o) completed self‐report measures of perceived stress, anxiety (state/sensitivity) and emotion regulation strategies (cognitive reappraisal/expressive suppression). Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 120 publications
0
1
0
2
Order By: Relevance
“…La COVID-19 ha traído consecuencias causando que padres de familia busquen apoyo para regular sus emociones, tanto para ellos mismos como para sus hijos. En este contexto es que los participantes de esta investigación solicitaron apoyo en calidad de urgencia, y por ello, se decide intervenir mediante educación a distancia debido a las circunstancias dadas en la pandemia como son la incertidumbre de la estabilidad laboral, la posible enfermedad, así como las responsabilidades del cuidado de los hijos y la casa, combinadas con teletrabajo, los llevaron a vivir un estrés difícil de manejar (Journault et al 2022;Rodas-Santos, et.al., 2020;Avello, 2020). Por ello, la pregunta de investigación que guía este trabajo fue: ¿cómo promover la RE.…”
Section: Marco Teóricounclassified
See 1 more Smart Citation
“…La COVID-19 ha traído consecuencias causando que padres de familia busquen apoyo para regular sus emociones, tanto para ellos mismos como para sus hijos. En este contexto es que los participantes de esta investigación solicitaron apoyo en calidad de urgencia, y por ello, se decide intervenir mediante educación a distancia debido a las circunstancias dadas en la pandemia como son la incertidumbre de la estabilidad laboral, la posible enfermedad, así como las responsabilidades del cuidado de los hijos y la casa, combinadas con teletrabajo, los llevaron a vivir un estrés difícil de manejar (Journault et al 2022;Rodas-Santos, et.al., 2020;Avello, 2020). Por ello, la pregunta de investigación que guía este trabajo fue: ¿cómo promover la RE.…”
Section: Marco Teóricounclassified
“…Ante el confinamiento los gobiernos tuvieron que aplicar medidas que facilitaran la educación a distancia (García Aretio 2020; Avello, 2020), si bien, con muchas problemáticas, también se observó beneficio a la comunidad educativa, ya que permitió una mejor organización de la información, uso de nuevos conceptos, distintas formas de intercambiar la información y el reenfoque de la importancia del trabajo con los padres de familia (Aguilar-Gordón, 2020;Journault et al 2022).…”
Section: Conclusionesunclassified
“…In fact, studies show an overestimation of the parents when rating children’s behaviors, resulting in assessment biases [ 44 ]. However, researchers have suggested that parent proxy forms are an excellent candidate for accurately detecting cognitive and emotional aspects in youngsters [ 45 ].…”
Section: Introductionmentioning
confidence: 99%